Accurate estimation of mixing time in a direct contact boiling heat transfer process using statistical methods. (July 2016) - Xu, Jianxin; Xiao, Qingtai; Fei, Yu; Wang, Shibo; Huang, Junwei
Abstract: A novel method relying on image analysis and statistics is developed to estimate the mixing time accurately in a direct-contact heat exchanger. The critical point determination of pseudo homogeneous process impact on the accurate estimation of mixing time is investigated by proposed a three-sigma (3σ) method, which satisfies approximately normal distribution and exceeding the range of μ  − 3σ occurring twice. Quantitative comparisons of the mixing time are conducted with mean value method, slope method and standard deviation method. Results show that correlation degree and correlation coefficient for the mixing time estimated by 3σ method give good agreement with the volumetric heat transfer coefficient average. Additionally, quasi steady state is quantified by time intervals between inhomogeneous time and mixing time. Experiments and simulations confirmed that neglecting critical point could result in significant errors in mixing time estimation. This method is capable of estimating the mixing time obtained by different mixing curves (e.g., slope p ) that vary at the beginning of mixing and rapidly become stabilized after fluctuations, which can be an alternative tool for practical engineering applications with good accuracy.